2021
DOI: 10.1080/21541264.2022.2047583
|View full text |Cite
|
Sign up to set email alerts
|

Emerging insights into the function and structure of the Integrator complex

Abstract: The Integrator was originally discovered as a specialized 3’-end processing endonuclease complex required for maturation of RNA polymerase II (RNAPII)-dependent small nuclear RNAs (snRNAs). Since its discovery, Integrator’s spectrum of substrates was significantly expanded to include non-polyadenylated long noncoding RNAs (lncRNA), enhancer RNAs (eRNAs), telomerase RNA (tertRNA), several Herpesvirus transcripts, and messenger RNAs (mRNAs). Recently emerging transcriptome-wide studies reveled an important role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 99 publications
(219 reference statements)
0
11
0
Order By: Relevance
“…Integrator complex assembles from fifteen canonical subunits (INTS1-15), including recently uncovered INTS15 [26][27][28][29][30] and together with PP2A-C heterodimer forms a 1.5 MDa Integrator-PP2A complex that harbours endonuclease (INTS11) and phosphatase (PP2A-C) enzymatic activities [31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrator complex assembles from fifteen canonical subunits (INTS1-15), including recently uncovered INTS15 [26][27][28][29][30] and together with PP2A-C heterodimer forms a 1.5 MDa Integrator-PP2A complex that harbours endonuclease (INTS11) and phosphatase (PP2A-C) enzymatic activities [31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…Integrator complex assembles from fifteen canonical subunits (INTS1-15), including recently uncovered INTS15 2630 and together with PP2A-C heterodimer forms a 1.5 MDa Integrator-PP2A complex that harbours endonuclease (INTS11) and phosphatase (PP2A-C) enzymatic activities 3134 . Numerous other factors have been reported to interact with the Integrator, most notably transcription regulators (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Various experiments showed that the Integrator complex assembles in a stepwise manner from separate stable modules including the shoulder module (INTS5/8), the backbone module (INTS1/2/7/12), the cleavage module (INTS4/9/11) and the ternary complex INTS10/13/14 which has been shown to bind RNA ( 47 , 48 ). Based on our finding that INTS10 levels decrease in patients’ cells, we first tested whether limited amounts of INTS10/13/14 are immunoprecipitated using anti-INTS13 antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Integrator-dependent premature termination is emerging as an integral way to regulate Pol II transcription 20 , 21 , 50 , but our understanding of how Integrator terminates Pol II is limited. Here we present three cryo-EM structures of the complete Integrator: one bound to the PEC in the pre-termination state; one bound to Pol II in the post-termination state; and one of the complete, free complex in an inactive state.…”
Section: Discussionmentioning
confidence: 99%
“…Integrator not only targets paused Pol II during the transcription of protein-coding genes, but is also involved in terminating the synthesis of noncoding Pol II transcripts, including enhancer RNAs 16 , small nuclear RNAs 17 , telomerase RNA 18 and long noncoding RNAs 19 . Indeed, Integrator is a genome-wide regulator of Pol II transcription 20 , 21 .…”
Section: Mainmentioning
confidence: 99%